1965
DOI: 10.1177/028418516500300209
|View full text |Cite
|
Sign up to set email alerts
|

Backward Luxation of the Atlas

Abstract: Backward luxation of the atlas would appear to be an extremely rare con dition. A number of authors mention the infrequency of backward luxation as compared to the more common forward luxation although no single unequiv ocal report of this condition could be found in an extensive study of the literature. According to MALGAIGNE (1) a case was described in 1850 by MELCHIORI in Italy ; it was not possible however to obtain the original of this paper. There would therefore appear to be some justification for the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1970
1970
1994
1994

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…We have been able to find in the world literature only one previous case, reported by Verjaal and Harder (1965). This patient, also suffering from chronic seropositive rheumatoid arthritis, was a 66-year-old housewife with widespread joint involvement and a high ESR, who had been treated with gold, salicylates, and pyridine derivatives.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…We have been able to find in the world literature only one previous case, reported by Verjaal and Harder (1965). This patient, also suffering from chronic seropositive rheumatoid arthritis, was a 66-year-old housewife with widespread joint involvement and a high ESR, who had been treated with gold, salicylates, and pyridine derivatives.…”
Section: Discussionmentioning
confidence: 92%
“…Verjaal and Harder (1965) did not present evidence to exclude the possibility that it was a rheumatoid nodule, rather than, as stated, a meningioma. For backward luxation of the atlas to occur the anterior arch of the atlas must be destroyed or congenitally absent, or the odontoid process must be fractured, destroyed, or congenitally absent.…”
Section: Casementioning
confidence: 89%
“…in the 5 previously described cases varied. In 2 of the patients, the odontoid process had been destroyed (4, 9). In one of these cases (9) the anterior arc of the atlas was also absent.…”
Section: Discussionmentioning
confidence: 99%
“…Review of necropsy reports of 12 patients who died of dislocation of C1 on C2 vertebra due to rheumatoid arthritis (Davis and Markley, 1951;Martel and Page, 1960;Martel and Abell, 1963;Gleason and Urist, 1965;Verjaal and Harder, 1965;Bland, 1967;Webb et al, 1968) shows that incompetence of the transverse ligament of C1 vertebra was found in only three patients (Martel and Abell, 1963;Webb et al, 1968). Of these three patients, two died of upper cervical cord compression from the displaced odontoid process (Martel and Abell, 1963).…”
Section: Discussionmentioning
confidence: 99%
“…Significant rheumatoid granulation tissue was found be-tween the anterior arch of C1 vertebra and the odontoid process on six occasions (Gleason and Urist, 1965;Bland, 1967), in the retro-odontoid space on two occasions (Martel and Abell, 1963;Gleason and Urist, 1965), and between C4 and C5 vertebrae on one occasion (Bland, 1967). In one patient backward dislocation of C1 vertebra due to rheumatoid process was associated with a large intraspinal meningioma attached to the body of C2 vertebra (Verjaal and Harder, 1965).…”
Section: Discussionmentioning
confidence: 99%